Will You Pay More for Sustainable Fashion Brands? Exploring the Factors Behind Sustainable Fashion Purchases - Inggang Perwangsa Nuralam; Intan Ayu Permatasari (Jurnal Manajemen Indonesia, 2025)
the high amount of textile waste produced in large quantities, excessive consumption patterns among the public and the use of materials that are not environmental friendly, including the many fashion brand businesses in Indonesia. This research was conducted to determine and explain the effect of social influence, environmental awareness, price, and eWOM on purchase intention and willingness to pay for sustainable fashion brands. The type of research used is explanatory research with quantitative approach. The population in this research were consumers who had an interest in purchase intention from sustainable fashion brands in Malang, with a sample of 230 respondents obtained through purposive sampling technique. The data collection method used an online questionnaire, and the data analysis technique used Partial Least Square-Structural Equation Modeling (PLS-SEM) using SMARTPLS Version 4.0 software. The test results show that social influence, environmental awareness, and price have a direct positive effect on purchase intention. Furthermore, purchase intention has a direct positive effect on eWOM and purchase intention has a direct positive effect on willingness to pay